PENDAMPINGAN PENDIDIKAN SUFISTIK SEBAGAI PENGUATAN MODERASI BERAGAMA MAHASISWA UIN KH. ACHMAD SIDDIQ JEMBER - Mas'ud Mas'ud ('Ibadatuna : Jurnal Pengabdian Masyarakat, 2026)
This study aims to analyze the mentoring of Sufistic education in strengthening the religious moderation attitudes of students at UIN Kiai Haji Achmad Siddiq Jember. The method used is qualitative, with data collection techniques consisting of observation, in-depth interviews, and documentation. The results show that the relationship between Sufistic values and religious moderation is manifested in three aspects: tolerance (mahabbah), a balanced stance (tawassuth), and ego control through self-reflection (muhasabah). Furthermore, religious moderation is strongly integrated with nationalism, where national commitment and acceptance of Pancasila as well as the Unitary State of the Republic of Indonesia (NKRI) are understood as the practice of religious teachings. The measurement of students' religious moderation attitudes is in the excellent category, with the primary indicator demonstrated through a willingness to accept diverse understandings and opinions of others